PENERAPAN ARTIFICIAL INTELLIGENCE (AI) DALAM DESAIN GRAFIS UNTUK MENINGKATKAN KREATIFITAS DAN INOVASI - Yunus Anis; Sri Mulyani; Sunardi Sunardi (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study discusses the application of artificial intelligence (AI) technology in the graphic design industry to enhance creativity and innovation. As technology advances, AI is increasingly being used to assist graphic designers in producing faster, more creative, and innovative designs. This study identifies how AI tools such as DALL-E and Canva can be used to simplify the design process, improve the quality of work, and accelerate innovation in graphic design. The results show that the use of AI can improve design efficiency, enrich design variations, and accelerate the process of generating new ideas. However, challenges such as limited creativity and understanding the design context remain issues that designers must overcome.